Emerging trends in the novel drug delivery approaches for the treatment of lung cancer. (25th August 2019) - Sharma, Parvarish; Mehta, Meenu; Dhanjal, Daljeet Singh; Kaur, Simran; Gupta, Gaurav; Singh, Harjeet; Thangavelu, Lakshmi; Rajeshkumar, S.; Tambuwala, Murtaza; Bakshi, Hamid A.; Chellappan, Dinesh Kumar; Dua, Kamal; et al.
Abstract: Cancer is one of the major diseases that cause a high number of deaths globally. Of the major types of cancers, lung cancer is known to be the most chronic form of cancer in the world. The conventional management of lung cancer includes different medical interventions like chemotherapy, surgical removal, and radiation therapy. However, this type of approach lacks specificity and also harms the adjacent normal cells. Lately, nanotechnology has emerged as a promising intervention in the management and treatment of lung cancers. Nanotechnology has revolutionized the existing modalities and focuses primarily on reducing toxicity and improving the bioavailability of anticancer drugs to the target tumor cells. Nanocarrier systems are being currently used extensively to exploit and to overcome the obstructions induced by cancers in the lungs. The nano-carrier-loaded therapeutic drug delivery methods have shown promising potential in treating lung cancer as its target is to control the growth of tumor cells. In this review, various modes of nano drug delivery options like liposomes, dendrimers, quantum dots, carbon nanotubes and metallic nanoparticles have been discussed. Nano-carrier drug delivery systems emerge as a promising approach and thus is expected to provide newer and advanced avenues in cancer therapeutics. Highlights: Lung cancer is one of the most prevalent form of cancer worldwide. Traditional treatment methods includes surgery, radiation and chemotherapy. Main side effects of existing treatments are nonspecific targeting and toxicity. Novel drug delivery offers improved bioavailability and site-specific targeting. Emerging trends in drug delivery will provide new direction to lung cancer clinics.